Gut pH, Histology and Microbial Enzymes Production of the Mouth and Stomach in Achatina achatina. - Okeniyi, F.A.; Oyebimpe, K.; Osinowo, O.A. (Nigerian Journal of Animal Science, 2026)
The African land snail, Achatina achatina digestive activities were studied by determining pH, gut morphology, and preparing microflora cultures from the gut content. The microorganisms within the digestive tract were isolated, identified and enzyme assays were carried out on two of the isolates to determine the presence and levels of enzyme activity. Results revealed that Bacillus aureus (from the stomach region), and Aeroccus viridians (from the mouth region) effectively digested starch, cellulose and casein. However, B. aureus from the stomach region exhibited the highest enzymatic activities for amylase (9.39μM/min/ml), cellulose (10.13μM/min/ml), and protease (24.23μM/min/ml) all at 18h of incubation. The study provided insight into gut micro-environment, morphology and bacteria activities aiding digestive processes within the gut of Achatina achatina. The enzymes production capabilities of the bacterial organisms isolated from the gut of A. achatina could find use in industrial production of items such as laundry detergents, paper, wine, biofuel and degradation of biomass.